PENGARUH EFIKASI DIRI, KOMPENSASI, DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA PEGAWAI BIDANG PROGRAM DAN EVALUASI PUSAT PENYULUHAN PERTANIAN, KEMENTERIAN PERTANIAN - Ghiffarin Sekar Ananditi (2022)
This study is a quantitative research that objectives to determine whether there is an effect of self-efficacy, compensation, also career development on job satisfaction of employees in the Program and Evaluation of Agricultural Extension Center. This research used 45 respondents, the sampling technique used was saturated sampling technique. In this research hypothesis, namely to determine the effect either partially or simultaneously of the variables X and Y, so that the tests used are the coefficient of determination test, f test and t test. Furthermore, the research results obtained are: (1) self-efficacy has a positive and significant effect on job satisfaction, (2) compensation has a positive and significant effect on job satisfaction, (3) career development has a positive and significant influence on job satisfaction. work, (4) self-efficacy, compensation, and career development have a significant effect on employee job satisfaction in the field of Program and Evaluation of Agricultural Extension Center. Keywords : Self-Efficacy, Compensation, Career Development and Job Satisfaction